Radziwiłł the Orphan’s Book Journey to Jerusalem: Aspects of Book Art in the Braniewo (1601) and Antwerp (1614) Editions - Liškevičienė, Jolita (Knygotyra, 2025)
This article examines two Latin editions of Mikołaj Krzysztof Radziwiłł the Orphan’s book Journey to Jerusalem (Ierosolymitana peregrinatio) – the Braniewo (1601) and Antwerp (1614) editions. It compares the illustrations, the book format, the title pages, and typographical elements of both editions. The comparison of these two book variants from the perspective of book art was made possible by the surviving and newly published correspondence between the patron, Jesuit Jan Aland, the publisher Balthasar Moretus, and Duke Radziwiłł’s trusted agent in Paris, Ottho van der Palen (Otto à Palen). A question is raised in the article why the Plantin-Moretus printing house was selected for the book’s publication when descriptions of the journey had already been printed in Latin, Polish, and German. This article also brings up and discusses more broadly the questions of book art and printing of that time, by comparing the production of local presses with one of the most renowned European printing houses at the time, namely, Plantin-Moretus.